Implementasi Hukum Ekonomi Syariah dalam Praktek Gadai Sawah - Hukmiah Hukmiah (FENOMENA, 2016)
This article is an attempt to find solutions to the problems of the Muslims who practice field pawn. Field pawn practiced that was conducted so far only based on local customs laws and is considered to deviate from the basic principles of Islamic economics, namely; help each other, the prohibition of using treasure with the falsehood and the ban on the practice of usury. Field pawn done with handed over the land / fields to others to be controlled temporarily with all their profits and in return he got a loan of cash, and the land will be returned when the loan is redeemed or repaid. Actually, the main function of the devolving of the land is a guaranty for the loan funds that is received by land owner, and consequently the land is at the authority of the lender, so all land use is in the right lender. Looking at from the contract side, field pawn carried out without the clear contract, on the one hand is borrowing and on the other hand is considered as buying and selling because the land owners do not have the right to use it except with the permission of the lender so that it is called buying and selling.